Efektivitas Terapi Akupresur Titik Pc 6 Dalam Mengatasi Emesis Gravidarum pada Ibu Hamil Trimester I di Puskesmas Wana Kec. Melinting - Desy Supiantari; Anissa Ermasari; Fijri Rachmawati; Ike Ate Yuviska (Malahayati Nursing Journal, 2024)
ABSTRACT Emesis gravidarum (morning nausea and vomiting) is a physiological change that occurs due to increased levels of the human chorionic gonadotropin (HCG) hormone produced by the placenta. As a complaint, nausea and vomiting are still considered normal, so disturbances during pregnancy are considered normal, but if this nausea and vomiting is excessive and continues without knowing the time, it can cause fluid disturbances (dehydration). One way to reduce emesis gravidarum is with acupressure therapy, point pc 6 .Based on data from pregnant women who visited from the beginning of January to February 2023 at the wana health center, there were 62 pregnant women on the first visit, and of the 62 k1 pregnant women there were 35 pregnant women who experienced nausea, vomiting or emesis gravidarum. The aim of this study was to find out the average The average level of emesis gravidarum in first trimester pregnant women at the wana health center in 2023 before and after being given PC 6 point acupressure. The method used was quantitative, the research design used the one group pre-test and post-test approach, with a population of 62 pregnant women and a sample of 30 respondents, conducted in July 2023. The sampling technique used purposive sampling, univariate and bivariate data analysis used test Wilcoxon. The results of the research conducted by the author show that there is an effect of applying PC 6 point acupressure on the level of emesis gravidarum in first trimester pregnant women at the sub-district health center. Rolls before being given the intervention and after being given the acupressure intervention at PC 6 point, with a p-value of 0.000 (0.005). The conclusion from the treatment of PC 6 point acupressure therapy on the emission of gravidarum in the 1st trimester of pregnant women at the Wana sub-district health center. Melinting in 2023 that there is an effect on the level of emesis gravidarum in first trimester pregnant women at the sub-district wana health center. Rolling and already effective. The role of health workers should pay more attention to the problem of emesis gravidarum in pregnant women and need training in pc 6 point acupressure techniques so that they are more competent so they can provide complete midwifery care. Keywords: PC 6 Point Acupressure, Emesis Gravidarum, Pregnant Women Trimester I  ABSTRAK Emesis gravidarum (mual muntah di pagi hari) merupakan salah satu perubahan fisiologis yang terjadi karena peningkatan kadar hormon Human chorionic gonandotropin (HCG) yang dihasilkan oleh plasenta. Sebagai keluhan mual muntah ini masih dianggap wajar sehingga gangguan selama kehamilan ini dianggap normal, namun mual muntah ini jika berlebihan dan terus menerus tanpa mengenal waktu maka bisa menimbulkan ganguan cairan (dehidrasi).Salah satu cara untuk mengurangi emesis gravidarum dengan terapi akupresur titik pc 6.Berdasarkan data ibu hamil yang berkunjung diawal bulan januari sampai dengan februari 2023 di puskesmas wana, sebanyak 62 ibu hamil kunjungan pertama, dan dari 62 ibu hamil k1 tersebut ada 35 ibu hamil yang mengalami mual muntah atau emesis gravidarum. Tujuan penelitian ini untuk diketahui rata-rata tingkat emesis gravidarum pada ibu hamil trimester 1 di puskesmas wana tahun 2023 sebelum dan sesudah diberikan akupresur titk PC 6. Metode yang digunankan adalah kuantitatif,desain penelitian menggunakan pendekatan the one group pre-tes dan post-tes,dengan populasi 62 ibu hamil dan sampel 30 responden, dilakukan di bulan juli 2023.Teknik sampling menggunakan purposive sampling,analisa data univariat dan bivariat menggunakan uji Wilcoxon. Hasil penelitian yang dilakukan oleh penulis bahwa ada pengaruh penerapan akupresur titik PC 6 terhadap tingkat emesis gravidarum pada ibu hamil trimester 1 di puskesmas wana kec. Melinting sebelum diberikan intervensi dan sesudah diberikan intevensi akupresur titik PC 6 yaitu dengan nilai p-value adalah 0.000 (0.005). Kesimpulan dari perlakuan terapi akupresur titik pc 6 terhadap emisis gravidarum ibu hamil trimester 1 di puskesmas wana kec. Melinting tahun 2023 bahwa ada pengaruh terhadap tingkat emesis gravidarum pada ibu hamil trimester 1 di puskesmas wana kec. Melinting dan sudah efektif.Peran petugas kesehatan hendaknya lebih memperhatikan masalah emesis gravidarum pada ibu hamil dan perlu pelatihan teknik akupresur titik pc 6 supaya lebih kompeten agar dapat memberikan asuhan kebidanan yang paripurna. Kata Kunci: Akupresur Titik PC 6, Emesis Gravidarum, Ibu Hamil Trimester